2019
DOI: 10.31557/apjcp.2019.20.11.3211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Exposure to Radar Radiation on Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: Objective: Microwave radiation is one of the most growing environmental workplace factors that exposes too many workers in the various workplaces. Regard to concerns about cancer incidence in these workers and lack of systematic or meta-analytic studies about this object, so, we conducted a meta-analysis to acquire an understanding of the association between cancer risk and occupational exposure to radar radiation. Methods: A systematic search was carried out on case-control, cohort and clinical control trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…French Navy personnel working near radar systems had similar all-cause and cancer-specific mortality as their unexposed peers, 32 and a meta-analysis concluded that occupational exposure to radar conveys no significant cancer risk if proper preventive measures are followed. 33 US Air Force ground crew are routinely exposed to ambient benzene, 34 an established leukemogen that may increase the risk of non-Hodgkin lymphoma. 35 However, among the most highly exposed group of fuel maintenance workers, pre-work breath concentrations in smokers exceeded post-work concentrations in non-smokers, 34 suggesting that recreational exposure to tobacco combustion may confound the relationship between occupational exposure to jet fuel combustion and cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…French Navy personnel working near radar systems had similar all-cause and cancer-specific mortality as their unexposed peers, 32 and a meta-analysis concluded that occupational exposure to radar conveys no significant cancer risk if proper preventive measures are followed. 33 US Air Force ground crew are routinely exposed to ambient benzene, 34 an established leukemogen that may increase the risk of non-Hodgkin lymphoma. 35 However, among the most highly exposed group of fuel maintenance workers, pre-work breath concentrations in smokers exceeded post-work concentrations in non-smokers, 34 suggesting that recreational exposure to tobacco combustion may confound the relationship between occupational exposure to jet fuel combustion and cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in more vulnerable military occupations, electromagnetic frequency and aromatic hydrocarbons are unlikely carcinogens for fighter aviators. French Navy personnel working near radar systems had similar all-cause and cancer-specific mortality as their unexposed peers, 32 and a meta-analysis concluded that occupational exposure to radar conveys no significant cancer risk if proper preventive measures are followed 33 . US Air Force ground crew are routinely exposed to ambient benzene, 34 an established leukemogen that may increase the risk of non-Hodgkin lymphoma 35 .…”
Section: Discussionmentioning
confidence: 99%